The New Educational Policy in India: Towards a Digital Future - Dr. Akhilesh A. Waoo; Dr. Ashwini A. Waoo (Journal La Edusci, 2021)
New Education Policy was formulated by the Government via a consultation process. It emerges as an inclusive, participatory, and holistic approach of MHRD initiated in January 2015, MHRDA new National Education Policy (NEP) has been approved by the Union Cabinet, which makes modifications in the Indian system of education from school to college. The New Education Policy outlines India's goal of becoming a knowledge superpower. As part of the restructuring, the Ministry of Human Resources Development (MHRD) became the Ministry of Education. NEP promotes ideas, concepts, applications, and problem-solving activities. This policy calls for more interactive teaching-learning. A technology-based educational approach is emphasized in this policy. This policy demonstrates a greater use of ICT for remote and interactive education at school and in higher education. The study in this paper shows the impact of ICT tools on future education and various methods for building virtual infrastructure for learning.